Dual-scale ceramic particle reinforced aluminum matrix composite material and preparation method thereof

CN116287911BActive Publication Date: 2025-02-25HUNAN JINTIAN ALUMINUM HI TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310209341.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-06-09
Filing Date
2023-03-07
Publication Date
2025-02-25
Estimated Expiration
2043-03-07

AI Technical Summary

Technical Problem

When the ceramic particle-reinforced aluminum-based composite materials increase the ceramic particle content, they are prone to defects such as uneven distribution of ceramic particles, low material density, and easy cracks, resulting in the inability to further improve the overall performance.

Method used

The double-scale ceramic particles (composed of fine ceramic particles and coarse ceramic particles with a mass ratio of 0.5 to 1.5) are mixed with aluminum alloy powder. By controlling the mass ratio and particle size distribution of ceramic particles, the uniform distribution of ceramic particles and the density of the material are achieved. .

Benefits of technology

The ceramic particle content is uniformly distributed within the range of 25% to 75%, the material density is high, and there are no defects such as cracks, and the comprehensive performance of temperature resistance, wear resistance, modulus, and dimensional stability is significantly improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to a dual-scale ceramic particle reinforced aluminum-based composite material and a preparation method thereof, wherein the composite material is prepared from 25% to 75% of ceramic particles and the remainder of aluminum alloy powder, wherein the ceramic particles are composed of fine ceramic particles and coarse ceramic particles in a mass ratio of (0.5 to 1.5): 1, and the D50 of the fine ceramic particles is 15 μm to 30 μm, the D50 of the coarse ceramic particles is 100 μm to 200 μm, and the D50 of the aluminum alloy powder is 15 μm to 30 μm. The above-mentioned composite material can achieve uniform distribution of ceramic particles when the content is adjusted within the range of 25% to 75%, and the material has high density, no defects such as cracks, and the comprehensive properties such as temperature resistance, wear resistance, modulus, and dimensional stability are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims the priority of the Chinese patent application filed with the China Patent Office on June 9, 2022, with application number 202210651237.0 and invention name “Dual-scale ceramic particle reinforced aluminum-based composite material and preparation method thereof”, the entire contents of which are incorporated by reference in this application. Technical Field

[0002] The invention relates to the technical field of aluminum-based composite materials, in particular to a dual-scale ceramic particle reinforced aluminum-based composite material and a preparation method thereof. Background Art

[0003] Ceramic particles have excellent properties such as high modulus, high wear resistance, high strength, low density and high temperature resistance. Aluminum or aluminum alloy has the advantages of light weight and good thermal conductivity. The composite of ceramic particles and aluminum or aluminum alloy can greatly improve the comprehensive performance of aluminum or aluminum alloy. The higher the content of ceramic particles, the more significant the reinforcement effect on aluminum or aluminum alloy. At present, most ceramic particle reinforced aluminum-based composite materials use ceramic particles of a single scale, and the particle size is generally 5 to 30 microns. However, with the increase of the content of single-scale ceramic particles, the compressibility of the powder deteriorates. When the particle size of the selected ceramic particles is less than 10 microns, with the increase of the content of ceramic particles, the fluidity of the powder will also deteriorate. The ceramic particles are easy to bridge to form a skeleton or local agglomeration. The matrix and the ceramic particles cannot form a sufficient interface bond, resulting in defects such as holes in the material and uneven distribution of ceramic particles, which in turn leads to the material's temperature resistance, thermal conductivity, high-temperature wear resistance, etc. cannot be further improved, limiting its application.

[0004] Using ceramic particles of various sizes as reinforcing phases can improve the filling properties of powders, increase the compressibility and loose density of powders, and improve the shortcomings of single-size ceramic particles as reinforcing phases, so that ceramic particles of different sizes can complement each other's advantages and produce a hybrid effect, thereby improving the material's temperature resistance, thermal conductivity, high-temperature wear resistance, etc. However, as the content of ceramic particles increases, there is still a problem of uneven distribution of ceramic particles. When large-scale ceramic particles are selected, large-scale ceramic particles are prone to defects such as brittle cracks, which makes it easy for stress concentration points to appear in the material, resulting in cracking, reduced strength and other problems, affecting the service life of the material. Summary of the invention

[0005] Based on this, it is necessary to provide a dual-scale ceramic particle reinforced aluminum-based composite material, which can achieve uniform distribution of ceramic particles when the content is adjusted within the range of 25% to 75%, and has high material density, no defects such as cracks, and good comprehensive performance.

[0006] A dual-scale ceramic particle reinforced aluminum-based composite material is prepared from 25% to 75% of ceramic particles and the remainder of aluminum alloy powder, in terms of mass percentage. The ceramic particles are composed of fine ceramic particles and coarse ceramic particles in a mass ratio of (0.5 to 1.5):1, the D50 of the fine ceramic particles is 15 μm to 30 μm, the D50 of the coarse ceramic particles is 100 μm to 200 μm, and the D50 of the aluminum alloy powder is 15 μm to 30 μm.

[0007] In one embodiment, the aluminum alloy powder is composed of 1% to 4% copper powder, 1% to 3% magnesium powder, 0 to 1% trace element powder and the remainder aluminum powder, measured in percentage by mass, and the trace element powder is selected from at least one of bismuth powder, iron powder and tin powder.

[0008] In one embodiment, the content of each trace element powder in the aluminum alloy powder is 0-0.5% by mass percentage.

[0009] The above-mentioned dual-scale ceramic particle reinforced aluminum-based composite material is prepared by using coarse ceramic particles with a D50 of 100 to 200 microns, fine ceramic particles with a D50 of 15 to 30 microns, and aluminum alloy powder with a D50 of 15 to 30 microns as raw materials. On the one hand, the coarse ceramic particles have good fluidity, and the fine ceramic particles have good strengthening effect. By controlling the mass ratio of coarse and fine ceramic particles, the material can have good compression performance and corresponding mechanical properties; on the other hand, the coarse ceramic particles have a large particle size and can play a pinning role. The fine ceramic particles and aluminum alloy powder have similar particle sizes and can be evenly distributed around the coarse ceramic particles to form an effective matrix distribution. During the preparation process, the aluminum alloy powder moves and deforms, ensuring the combination effect of coarse and fine ceramic particles and the matrix. The two aspects work together to achieve that the ceramic particles can always be evenly distributed when the content is adjusted within the range of 25% to 75%, and the material has high density, no defects such as cracks, and good comprehensive properties such as temperature resistance, wear resistance, modulus, and dimensional stability.

[0010] The present application also provides a method for preparing the above-mentioned dual-scale ceramic particle reinforced aluminum-based composite material, the specific scheme is as follows:

[0011] Providing the coarse ceramic particles, fine ceramic particles and aluminum alloy powder;

[0012] The coarse ceramic particles, fine ceramic particles and aluminum alloy powder are uniformly mixed according to a certain proportion, and then molded, sintered and shaped in sequence.

[0013] In one embodiment, the step of uniformly mixing the coarse ceramic particles, fine ceramic particles and aluminum alloy powder in proportion is specifically as follows: after uniformly mixing the fine ceramic particles and aluminum alloy powder in proportion, adding the coarse ceramic particles in proportion and continuing to mix evenly.

[0014] In one embodiment, the time for uniformly mixing the fine ceramic particles and the aluminum alloy powder is 5 to 10 minutes, and the rotation speed is 15 r / min to 30 r / min; the time for uniformly mixing the coarse ceramic particles is 30 to 60 minutes, and the rotation speed is 15 r / min to 30 r / min.

[0015] In one embodiment, the step of heating the mold is further included before the compression molding.

[0016] In one embodiment, the compression molding pressure is 200 MPa to 400 MPa.

[0017] In one embodiment, the sintering is performed in a protective gas atmosphere at a temperature of 560°C to 640°C.

[0018] In one embodiment, the shaping temperature is 500°C to 560°C.

[0019] The composite material prepared by the above method can achieve uniform distribution of ceramic particles when the content is adjusted from 25% to 75%, and the material has high density and no defects such as cracks. The comprehensive properties such as wear resistance, abrasion resistance, modulus, and dimensional stability are effectively improved. DETAILED DESCRIPTION

[0020] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below, and preferred embodiments of the present invention are provided. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0022] A dual-scale ceramic particle reinforced aluminum-based composite material in one embodiment is prepared from 25% to 75% by mass of ceramic particles and the remainder of aluminum alloy powder (the total mass content of the ceramic particles and the aluminum alloy powder is 100%), wherein the ceramic particles are composed of fine ceramic particles and coarse ceramic particles in a mass ratio of (0.5 to 1.5):1, and the D50 of the fine ceramic particles is 15μm to 30μm, the D50 of the coarse ceramic particles is 100μm to 200μm, and the D50 of the aluminum alloy powder is 15μm to 30μm.

[0023] In this embodiment, aluminum alloy powder is used as a matrix, preferably an aluminum alloy powder composed of 1% to 4% by mass of copper powder, 1% to 3% by mass of magnesium powder, 0 to 1% by mass of trace element powder and the remainder of aluminum powder (the total mass content of copper powder, magnesium powder, trace element powder and aluminum powder is 100%), wherein the trace element powder is selected from at least one of bismuth (Bi) powder, iron (Fe) powder and tin (Sn) powder.

[0024] Furthermore, the mass content of each trace element powder does not exceed 0.5%.

[0025] The appropriate amount of trace elements can improve the wettability between the aluminum alloy matrix and the ceramic particles. In addition, when Fe is selected as a trace element, a small amount of heat-resistant strengthening phase can be generated, further improving the heat resistance of the composite material.

[0026] In this embodiment, the coarse ceramic particles and the fine ceramic particles are used as the reinforcing phase, and their types are not particularly limited. Any ceramic particles well known to those skilled in the art can be used, such as carbides (TiC, SiC, B 4 C, etc.), nitride (Si 3 N 4 etc.), oxides (Al 2 O 3 etc.), silicide (Ti 5 Si 3 etc.), borides (TiB, TiB 2 Further, the coarse ceramic particles and the fine ceramic particles are preferably the same type of ceramic particles.

[0027] The above-mentioned dual-scale ceramic particle reinforced aluminum-based composite material is prepared by using coarse ceramic particles with a D50 of 100 to 200 microns, fine ceramic particles with a D50 of 15 to 30 microns, and aluminum alloy powder with a D50 of 15 to 30 microns as raw materials. On the one hand, the coarse ceramic particles have good fluidity, and the fine ceramic particles have good strengthening effect. By controlling the mass ratio of coarse and fine ceramic particles, the material can have good compression performance and corresponding mechanical properties; on the other hand, the coarse ceramic particles have a large particle size and can play a pinning role. The fine ceramic particles and aluminum alloy powder have similar particle sizes and can be evenly distributed around the coarse ceramic particles to form an effective matrix distribution. During the preparation process, the aluminum alloy powder moves and deforms, ensuring the combination effect of coarse and fine ceramic particles and the matrix. The two aspects work together to achieve uniform distribution of ceramic particles when the content is adjusted within the range of 25% to 75%, and the material has high density, no defects such as cracks, and good comprehensive properties such as temperature resistance, wear resistance, modulus, and dimensional stability.

[0028] The present invention also provides a method for preparing the above-mentioned dual-scale ceramic particle reinforced aluminum-based composite material, comprising the following steps S110 to S120:

[0029] S110, providing coarse ceramic particles, fine ceramic particles and aluminum alloy powder.

[0030] It should be noted that the above raw materials can be directly purchased or prepared by any method known in the prior art, as long as coarse ceramic particles with a D50 of 100 to 200 microns, fine ceramic particles with a D50 of 15 to 30 microns, and aluminum alloy powder with a D50 of 15 to 30 microns can be obtained.

[0031] S120, after uniformly mixing the above-mentioned coarse ceramic particles, fine ceramic particles and aluminum alloy powder according to a certain proportion, carry out molding, sintering and shaping in sequence.

[0032] Since the particle sizes of coarse ceramic particles, fine ceramic particles and aluminum alloy powder are quite different, and the fluidity of coarse ceramic particles is good, in this embodiment, it is preferred to mix the above raw materials in a mixing tank. Specifically, after the fine ceramic particles and aluminum alloy powder are evenly mixed in proportion, the coarse ceramic particles are added in proportion and continue to mix evenly. The time for mixing the fine ceramic particles and aluminum alloy powder evenly is 5 to 10 minutes, and the rotation speed is 15r / min to 30r / min; the time for adding the coarse ceramic particles and continuing to mix evenly is 30 to 60 minutes, and the rotation speed is 15r / min to 30r / min.

[0033] By first mixing the fine ceramic particles with the aluminum alloy powder and then adding the coarse ceramic particles to continue mixing, problems such as the generation of small particles due to long-term mixing of the coarse ceramic particles and the segregation of the fine ceramic particles and the aluminum alloy powder due to the large difference in particle size between the fine ceramic particles and the coarse ceramic particles can be avoided. The fine ceramic particles and the aluminum alloy powder are distributed around the coarse ceramic particles to form an effective matrix distribution.

[0034] In this embodiment, the pressure of the compression molding is 200 MPa to 400 MPa. During the compression molding process, the aluminum alloy powder moves and deforms, and is effectively filled between the coarse ceramic particles and the fine ceramic particles, thereby ensuring the density of the compact.

[0035] Furthermore, in order to improve the plasticity of the matrix during the powder forming stage, a step of heating the mold is included before the compression molding step, and the temperature of the mold after heating is 100°C to 200°C.

[0036] In this embodiment, sintering is performed in a protective gas atmosphere, such as nitrogen, argon, etc., and the sintering temperature is 560° C. to 640° C. During the sintering process, the aluminum alloy powder is further softened and forms a liquid phase, further improving the density of the material.

[0037] Furthermore, the shaping temperature is 500°C to 560°C.

[0038] The above preparation method, by first mixing a certain proportion of fine ceramic particles and aluminum alloy powder, and then adding coarse ceramic particles in proportion and continuing to mix, can make the fine ceramic particles and aluminum alloy powder form an effective matrix distribution around the coarse ceramic particles, and then through subsequent molding, sintering and shaping, it can be achieved that the ceramic particle content is always evenly distributed when adjusted within the range of 25% to 75%, and the material has high density, no defects such as cracks, and good comprehensive performance.

[0039] The following are specific embodiments.

[0040] Example 1

[0041] Prepare raw materials: fine SiC particles with D50 of 15μm, coarse SiC particles with D50 of 100μm, aluminum alloy powder with D50 of 15μm (composed of 2wt% Cu powder, 2wt% Mg powder, 0.5wt% Fe powder, 0.2wt% Bi powder, 0.3wt% Sn powder and the remainder Al powder), with a mass ratio of 1.5:1:7.5.

[0042] At a rotation speed of 15 r / min, fine SiC particles and aluminum alloy powder were mixed for 10 minutes, and then coarse SiC particles were added and mixed for 60 minutes to obtain a mixed material;

[0043] The mixed material is molded at 200 MPa, sintered at 560° C., and finally shaped at 500° C. to obtain a dual-scale ceramic particle reinforced aluminum-based composite material with a ceramic particle mass content of 25%.

[0044] After testing, the aluminum-based composite material prepared in Example 1 has a density of 99.5%, a tensile strength of 340 MPa, a uniform structure, and no agglomeration of particles.

[0045] Comparative Example 1

[0046] Comparative Example 1 is substantially the same as Example 1, except that the D50 of the coarse SiC particles in Comparative Example 1 is 220 μm.

[0047] After testing, the density of the aluminum-based composite material prepared in Comparative Example 1 was 98%, and the tensile strength was 280 MPa. This is because the coarse SiC particles were too large, their distribution was too dispersed, and the coarse SiC particles were more likely to break, reducing the strength of the composite material.

[0048] Comparative Example 2

[0049] Comparative Example 2 is substantially the same as Example 1, except that in Comparative Example 2, the D50 of the fine SiC particles is 12 μm, and the D50 of the aluminum alloy powder is 12 μm.

[0050] After testing, the density of the aluminum-based composite material prepared in Comparative Example 2 reached 98.8%, and the tensile strength reached 320 MPa. This is because the fine SiC and aluminum alloy powders are too fine, resulting in poor fluidity of the aluminum-based composite material powder, which leads to pores and uneven density in the composite material.

[0051] Comparative Example 3

[0052] Comparative Example 3 is substantially the same as Example 1, except that in Comparative Example 3, the mass ratio of the coarse SiC particles to the fine SiC particles is 3:1.

[0053] After testing, the density of the aluminum-based composite material prepared in Comparative Example 3 reached 97.5% and the strength reached 243 MPa. This is because the excessive amount of coarse SiC reduced the compressibility of the powder, and the reduced content of fine SiC weakened the strengthening effect of SiC on the aluminum-based composite material, resulting in a decrease in the density and strength of the composite material.

[0054] Example 2

[0055] Preparation raw materials: fine ceramic particles with a D50 of 30 μm, coarse ceramic particles with a D50 of 200 μm, and aluminum alloy powder with a D50 of 30 μm (composed of 3wt% Cu powder, 1.5wt% Mg powder and the remainder Al powder), with a mass ratio of 0.5:1:0.5.

[0056] The fine ceramic particles and the aluminum alloy powder were mixed for 5 minutes at a rotation speed of 30 r / min, and then the coarse ceramic particles were added and mixed for 30 minutes to obtain a mixed material.

[0057] The mixed material is molded at 400 MPa, sintered at 640° C., and finally shaped at 560° C. to obtain a dual-scale ceramic particle reinforced aluminum-based composite material with a ceramic particle mass content of 75%.

[0058] After testing, the aluminum-based composite material has a density of 99.0%, a strength of 200 MPa, a material modulus of 210 GPa, a uniform structure, no agglomeration of particles, and no obvious pores.

[0059] Example 3

[0060] Prepare raw materials: fine ceramic particles with D50 of 20μm, coarse ceramic particles with D50 of 150μm, aluminum alloy powder with D50 of 20μm (composed of 1wt% Cu powder, 1wt% Mg powder, 0.5wt% Bi powder, 0.2wt% Sn powder and the remainder Al powder), with a mass ratio of 0.5:1:0.5.

[0061] The fine ceramic particles and the aluminum alloy powder were mixed for 8 minutes at a rotation speed of 20 r / min, and then the coarse ceramic particles were added and mixed for 45 minutes to obtain a mixed material.

[0062] The mixed material is molded at 300 MPa, sintered at 600° C., and finally shaped at 520° C. to obtain a dual-scale ceramic particle reinforced aluminum-based composite material with a ceramic particle mass content of 75%.

[0063] After testing, the aluminum-based composite material has a density of 99.2%, a strength of 220 MPa, a material modulus of 22 GPa, a uniform structure, no agglomeration of particles, and no obvious pores.

[0064] Example 4

[0065] Prepare raw materials: fine ceramic particles with D50 of 15μm, coarse ceramic particles with D50 of 100μm, aluminum alloy powder with D50 of 15μm (composed of 1wt% Cu powder, 1wt% Mg powder, 0.5wt% Fe powder and the remainder Al powder), with a mass ratio of 1.5:1:7.5.

[0066] The fine ceramic particles and the aluminum alloy powder were mixed for 10 minutes at a rotation speed of 15 r / min, and then the coarse ceramic particles were added and mixed for 60 minutes to obtain a mixed material.

[0067] The mixed material is molded at 200 MPa, sintered at 560° C., and finally shaped at 500° C. to obtain a dual-scale ceramic particle reinforced aluminum-based composite material with a ceramic particle mass content of 25%.

[0068] After testing, the aluminum-based composite material has a density of 99.5%, a strength of 340 MPa, a uniform structure, and no agglomeration of particles.

[0069] Example 5

[0070] Preparation raw materials: fine ceramic particles with D50 of 30μm, coarse ceramic particles with D50 of 200μm, aluminum alloy powder with D50 of 30μm (composed of 4wt% Cu powder, 3wt% Mg powder, 1wt% Sn powder and the remainder Al powder), with a mass ratio of 1:1:1.

[0071] The fine ceramic particles and the aluminum alloy powder were mixed for 8 minutes at a rotation speed of 25 r / min, and then the coarse ceramic particles were added and mixed for 50 minutes to obtain a mixed material.

[0072] The mixed material is molded at 350 MPa, sintered at 620° C., and finally shaped at 520° C. to obtain a dual-scale ceramic particle reinforced aluminum-based composite material with a ceramic particle mass content of 66.7%.

[0073] After testing, the aluminum-based composite material has a density of 99.3%, a strength of 240MPa, a material modulus of 200GPa, a uniform structure, no agglomeration of particles, and no obvious pores.

[0074] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A dual-scale ceramic particle reinforced aluminum matrix composite material, characterized in that: The invention is prepared by 25% to 75% of ceramic particles and the remainder of aluminum alloy powder in terms of mass percentage, wherein the ceramic particles are composed of fine ceramic particles and coarse ceramic particles in a mass ratio of (0.5 to 1.5):1, the D50 of the fine ceramic particles is 15 μm to 30 μm, the D50 of the coarse ceramic particles is 100 μm to 200 μm, and the D50 of the aluminum alloy powder is 15 μm to 30 μm; The preparation method of the dual-scale ceramic particle reinforced aluminum-based composite material comprises the following steps: Providing the coarse ceramic particles, fine ceramic particles and aluminum alloy powder; The coarse ceramic particles, fine ceramic particles and aluminum alloy powder are mixed uniformly according to a certain proportion, and then molded, sintered and shaped in sequence; The step of uniformly mixing the coarse ceramic particles, the fine ceramic particles and the aluminum alloy powder in proportion is specifically: after uniformly mixing the fine ceramic particles and the aluminum alloy powder in proportion, adding the coarse ceramic particles in proportion and continuing to mix uniformly; The time for uniformly mixing the fine ceramic particles and the aluminum alloy powder is 5 to 10 minutes, and the rotation speed is 15 r / min to 30 r / min; the time for uniformly mixing after adding the coarse ceramic particles is 30 to 60 minutes, and the rotation speed is 15 r / min to 30 r / min.

2. The dual-scale ceramic particle reinforced aluminum matrix composite material according to claim 1, characterized in that: In terms of mass percentage, the aluminum alloy powder consists of 1% to 4% copper powder, 1% to 3% magnesium powder, 0 to 1% trace element powder and the balance aluminum powder, and the trace element powder is selected from at least one of bismuth powder, iron powder and tin powder.

3. The dual-scale ceramic particle reinforced aluminum matrix composite material according to claim 2, characterized in that: In terms of mass percentage, the content of each trace element powder in the aluminum alloy powder is 0 to 0.5%.

4. The dual-scale ceramic particle reinforced aluminum matrix composite material according to claim 1, characterized in that: The method also includes heating the mold before the compression molding.

5. The dual-scale ceramic particle reinforced aluminum matrix composite material according to claim 1, characterized in that: The pressure of the compression molding is 200MPa to 400MPa.

6. The dual-scale ceramic particle reinforced aluminum matrix composite material according to claim 1, characterized in that: The sintering is carried out in a protective gas atmosphere at a temperature of 560°C to 640°C.

7. The dual-scale ceramic particle reinforced aluminum matrix composite material according to claim 1, characterized in that: The shaping temperature is 500°C to 560°C.

Citation Information

Patent Citations

  • Preparation method for dual-scale SiC particle reinforced aluminum-based composite material

    CN107904452A

  • Method for preparing particle-reinforced aluminum-based composite material adopting hot-pressing sintering under atmospheric atmosphere

    CN109439940A

  • Powder for metallurgy and method for manufacturing molded product using said powder for metallurgy

    CN110121392A

  • Radiation shielding composition and method of making the same

    US20170335433A1